Universidade aberta do Brasil: polo de apoio presencial no município de foz do Iguaçu - PR - Balzzan, Edilson Carlos (2012)
The Open University of Brazil - UAB is a federal action, executed on the initiative of the Ministry of Education, working in collaborative network through the participation of Universities and Public Support Face Poles scattered in various regions of the country. Acting in higher education, and expand the supply of vacancies, has priority as a vocation to devote efforts in training primary school teachers. Being a relatively new program is being adapted and institutionalization, a fact that demands study, reflection and research. From this perspective, this thesis aims to understand the Open University of Brazil from the work done at the Polo Support Face of Foz do Iguaçu, Paraná State. For this purpose we conducted a rescue of the main experiences built in Brazil in the distance from 1889 and also the main laws relating to distance education, taking as its starting point the LDB 9394/1996. From the proposed objective, it was possible to verify the presence of three points that summarize the challenges to be overcome by the centers to Face Support: Financial sustainability, developing a management model and characterization of the Polo to the community as an educational space in higher education.